Diasporic Hallyu The Korean Wave in Korean Canadian Youth Culture - Yoon, Kyong (East Asian Popular Culture, 2022)
This open access book examines the lived experiences of diasporic Korean youth in light of the transnational flows of South Korean popular culture, known as the Korean Wave, or Hallyu. Drawing on an ethnographic study of Korean Canadian youth and their engagement with the Korean Wave, the book proposes a critical understanding of the interactions between diasporic youth audiences and popular culture. By examining the Korean Wave as diasporic cultural practices rather than the diffusion of national cultural products, the book reveals the diversified ways in which cultural flows are negotiated by audiences who take up relatively ambivalent reception positions between two or more national and cultural contexts. This book expands the scope of transnational audience studies and youth cultural studies by focusing attention on the diasporic media practices of young people.